TEACHING ENGLISH VOCABULARY ACQUISTION THROUGH GESTURE - Novi Riani; Diah Paramita Sari (INOVISH JOURNAL, 2020)
Abstract: Teaching vocabulary has been integrated in four skills: listening, speaking, reading, and writing. Most of the students always got low mark in the English test. After the researcher interviewed them, the problem was that they do not understand about the meaning of the vocabularies in the text. This research was literature study. The main objective of this research was to explain how far the strategy of using Gesture. The data in this study were collected through observation, documentation book, journal, and internet.Â  Based on the data analyzed, it can be concluded that gesture can be appliedÂ  in teaching vocabulary. There are four categories using gesture; 1) Iconic Gesture; 2) Metaphoric Gesture; 3)Deictic Gesture; 4) Beat Gesture.